МОДЕЛЬ БЕЗКОНТАКТНОЇ ЕЛЕКТРИЧНОЇ МАШИНИЗІ ЗБУДЖЕННЯМ ВІД ПОСТІЙНИХ МАГНІТІВ - Макарчук, О.В. (Інститут електродинаміки НАН України, Київ, 2010)
The mathematical model of electromechanical system "the contactless electric machine – the position rotor sensor – semiconductor rectifier or inverter" is considered. The comparative analysis of calculation results and experimental data is made. References 6, figures 4.